PENDAMPINGAN PROSES PRODUKSI HALAL (PPH) BAGI PELAKU USAHA (UMK) DI DESA WISATA DI KOTA KEDIRI - Siti Aminah; Siti Mahmudah; Nur Evi Maritiani (Jurnal Abdi Masyarakat, 2026)
Village tourism is a form of tourism that highlights rural authenticity, including natural scenery, culinary products, souvenirs, and homestays. One of the challenges faced by Micro and Small Enterprises (UMK) in tourism villages in Kediri City is the limited understanding of halal certification, particularly regarding the Self Declare scheme through the Free Halal Certification Program (SEHATI). Many UMK actors are only familiar with the regular certification pathway through Halal Inspection Bodies (LPH) and experience difficulties accessing and operating the BPJPH SiHalal system. This community service activity aims to enhance UMK actors’ understanding of Law No. 33 of 2014 on Halal Product Assurance, increase knowledge and skills in accessing halal certification through the Self Declare pathway, and support the issuance of halal certificates. The method used was mentoring and assistance in the Halal Production Process (PPH). The results show that 20 UMK actors successfully obtained halal certificates, contributing to increased consumer trust, market reach, and business competitiveness.